Stability and detectability of testosterone esters in dried blood spots after intramuscular injections. Issue 11 (12th July 2021) - Solheim, Sara Amalie; Levernæs, Maren Christin Stillesby; Mørkeberg, Jakob; Juul, Anders; Upners, Emmie N.; Nordsborg, Nikolai Baastrup; Dehnes, Yvette
Abstract: While misuse of testosterone esters is widespread in elite and recreational sports, direct detection of intact testosterone esters in doping control samples is hampered by the rapid hydrolysis by esterases present in the blood. With dried blood spot (DBS) as sample matrix, continued degradation of the esters is avoided due to inactivation of the hydrolase enzymes in dried blood. Here, we have developed the method further for detection of testosterone esters in DBS with focus on robustness and applicability in doping control. To demonstrate the method's feasibility, DBS samples from men receiving two intramuscular injections of Sustanon® 250 ( n  = 9) or placebo ( n  = 10) were collected, transported, and stored prior to analysis, to mimic a doping control scenario. The presented nanoLC‐HRMS/MS method appeared reliable and suitable for direct detection of four testosterone esters (testosterone decanoate, isocaproate, phenylpropionate, and propionate) after extraction from DBS. Sustanon® was detected in all subjects for at least 5 days, with detection window up to 14 days for three of the esters. Evaluation of analyte stability showed that while storage at room temperature is tolerated well for a few days, testosterone esters are highly stable (>18 months) in DBS when stored in frozen conditions. Collectively, these findings demonstrate the applicability of DBS sampling in doping control for detection of steroid esters. The fast collection and reduced shipment costs of DBS compared with urine and standard blood samples, respectively, will allow more frequent and/or large‐scale testing to increase detection and deterrence. Abstract : We further developed the Dried Blood Spot (DBS) methodology for detection of four testosterone esters with focus on robustness and applicability in doping control. The study consisted of two parts: method development and validation, and a human administration study with intramuscular injections of 250 mg Sustanon® in healthy men.